2017
DOI: 10.3892/ol.2017.7362
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a ketogenic diet with concomitant intranasal perillyl alcohol as a novel strategy for the therapy of recurrent glioblastoma

Abstract: Abstract. It has been hypothesized that persistent ketotic hypoglycemia represents a potential therapeutic strategy against high-grade gliomas. Perillyl alcohol (POH) is a non-toxic, naturally-occurring, hydroxylated monoterpene that exhibits cytotoxicity against temozolomide-resistant glioma cells, regardless of O6-methylguanine-methyltransferase promoter methylation status. The present study aimed to evaluate the toxicity and therapeutic efficacy of intranasal POH when administered in combination with a keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 46 publications
2
60
0
1
Order By: Relevance
“…However, perillic acid, the primary metabolite of POH, was easily measurable during PK studies of oral POH in cancer patients, and was shown to reach peak levels (C max ) of 600-770 μM. 7,8,11,12 Our current study is focused on pharmacology of POH and, most importantly, the introduction of a novel method that allows the simultaneous detection and measurement of POH and perillic acid. 5,31,32 Importantly, in the present work a methodology of HPLC-UV chromatography was developed and applied, which simultaneously determined the presence of POH and its metabolite PA in Wistar rats after inhalation of POH.…”
Section: Analysis Of Actual Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, perillic acid, the primary metabolite of POH, was easily measurable during PK studies of oral POH in cancer patients, and was shown to reach peak levels (C max ) of 600-770 μM. 7,8,11,12 Our current study is focused on pharmacology of POH and, most importantly, the introduction of a novel method that allows the simultaneous detection and measurement of POH and perillic acid. 5,31,32 Importantly, in the present work a methodology of HPLC-UV chromatography was developed and applied, which simultaneously determined the presence of POH and its metabolite PA in Wistar rats after inhalation of POH.…”
Section: Analysis Of Actual Samplesmentioning
confidence: 99%
“…A similar outcome was reported by Xu et al 6 after POH treatment of H322 and H838 lung cancer cell lines. 9,10 As an alternative to oral dosing, two clinical studies in Brazil 11,12 pioneered inhalational administration of POH and demonstrated that this approach was feasible and very well tolerated. 7,8 However, clinical trials with oral dosing of POH were disappointing, because the large number of capsules (gram quantities) that had to be swallowed 3-4 times a day on a continuous basis caused unrelenting grade 1 and grade 2 gastrointestinal (GI) effects and fatigue, which proved to be limiting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PA also has the advantage of being a treatment agent of herbal origin which is generally conceived as being safe by the general populace and has minimal side effects as compared to conventional drugs used in PD therapy. In recent times, PA has been used to treat a variety of disorders (Rodriguez, Carvalho, Kimura, & Katzin, ; Santos et al, ), but there are no reports of it being utilized in a PD model system yet.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, PA has been used to treat a variety of disorders (Rodriguez, Carvalho, Kimura, & Katzin, 2018;Santos et al, 2018), but there are no reports of it being utilized in a PD model system yet.…”
Section: Introductionmentioning
confidence: 99%